Clear aligners - knowledge and preference among parents of children aged 10 - 17 years - Haridasan, Ajith Kumar; Srinivasan, Ila; V. Setty, Jyothsna; Srinivasan, Smrithi; S. , Shilpa (International Journal of Contemporary Pediatrics, 2023)
Background: Clear aligners were introduced in the 20th century, but it did not gain popularity since there was a lack of promotion. However, now due to the widespread marketing on social media, clear aligners have gained popularity. Yet, the awareness about different types of clear aligners among parents was ambiguous. The aim of this study was to evaluate the knowledge and acceptance of clear aligners among the parents of children aged 10- 17 years. Methods: The study was conducted on 50 parents of children aged between 10 to 17 years in Bengaluru. A Questionnaire was given to the parents to assess their knowledge about various orthodontic treatments and the different types of clear aligners. A video was shown to the parents which explained about the ideal age for orthodontic treatment, types of clear aligners, their advantages and disadvantages. After the video-demonstration, a questionnaire was given to the parents to assess their preference. Results: On an average, the knowledge about different types of clear aligners among parents were low. Most of the parents were indecisive about choosing between In-office aligners and At-home aligners and unaware about the complications of At-home aligners. The study results showed that after video-demonstration, there was a statistically significant increase in the number of parents who chose ‘In-Office’ aligners over ‘At-home’ aligners (Mean value – 4.02). Conclusions: This study helped in creating awareness about In-Office aligners, the various complications of At-Home aligners and also educated the parents in choosing a better treatment option for their children.